Step
*
2
of Lemma
Taylor-remainder-as-integral
1. I : Interval
2. iproper(I)
3. a : {a:ℝ| a ∈ I} 
4. b : {a:ℝ| a ∈ I} 
5. [rmin(a;b), rmax(a;b)] ⊆ I 
6. n : ℤ
7. 0 < n
8. ∀F:ℕ(n - 1) + 2 ⟶ I ⟶ℝ
     ((∀k:ℕ(n - 1) + 2. ∀x,y:{a:ℝ| a ∈ I} .  ((x = y) 
⇒ (F[k;x] = F[k;y])))
     
⇒ finite-deriv-seq(I;(n - 1) + 1;i,x.F[i;x])
     
⇒ (Taylor-remainder(I;n - 1;b;a;k,x.F[k;x]) = a_∫-b (F[(n - 1) + 1;t]/r((n - 1)!)) * b - t^n - 1 dt))
9. F : ℕn + 2 ⟶ I ⟶ℝ
10. ∀k:ℕn + 2. ∀x,y:{a:ℝ| a ∈ I} .  ((x = y) 
⇒ (F[k;x] = F[k;y]))
11. finite-deriv-seq(I;n + 1;i,x.F[i;x])
⊢ Taylor-remainder(I;n;b;a;k,x.F[k;x]) = a_∫-b (F[n + 1;t]/r((n)!)) * b - t^n dt
BY
{ Assert ⌜λt.((F[n + 1;t]/r((n)!)) * b - t^n) ∈ {f:[rmin(a;b), rmax(a;b)] ⟶ℝ| ifun(f;[rmin(a;b), rmax(a;b)])} ⌝⋅ }
1
.....assertion..... 
1. I : Interval
2. iproper(I)
3. a : {a:ℝ| a ∈ I} 
4. b : {a:ℝ| a ∈ I} 
5. [rmin(a;b), rmax(a;b)] ⊆ I 
6. n : ℤ
7. 0 < n
8. ∀F:ℕ(n - 1) + 2 ⟶ I ⟶ℝ
     ((∀k:ℕ(n - 1) + 2. ∀x,y:{a:ℝ| a ∈ I} .  ((x = y) 
⇒ (F[k;x] = F[k;y])))
     
⇒ finite-deriv-seq(I;(n - 1) + 1;i,x.F[i;x])
     
⇒ (Taylor-remainder(I;n - 1;b;a;k,x.F[k;x]) = a_∫-b (F[(n - 1) + 1;t]/r((n - 1)!)) * b - t^n - 1 dt))
9. F : ℕn + 2 ⟶ I ⟶ℝ
10. ∀k:ℕn + 2. ∀x,y:{a:ℝ| a ∈ I} .  ((x = y) 
⇒ (F[k;x] = F[k;y]))
11. finite-deriv-seq(I;n + 1;i,x.F[i;x])
⊢ λt.((F[n + 1;t]/r((n)!)) * b - t^n) ∈ {f:[rmin(a;b), rmax(a;b)] ⟶ℝ| ifun(f;[rmin(a;b), rmax(a;b)])} 
2
1. I : Interval
2. iproper(I)
3. a : {a:ℝ| a ∈ I} 
4. b : {a:ℝ| a ∈ I} 
5. [rmin(a;b), rmax(a;b)] ⊆ I 
6. n : ℤ
7. 0 < n
8. ∀F:ℕ(n - 1) + 2 ⟶ I ⟶ℝ
     ((∀k:ℕ(n - 1) + 2. ∀x,y:{a:ℝ| a ∈ I} .  ((x = y) 
⇒ (F[k;x] = F[k;y])))
     
⇒ finite-deriv-seq(I;(n - 1) + 1;i,x.F[i;x])
     
⇒ (Taylor-remainder(I;n - 1;b;a;k,x.F[k;x]) = a_∫-b (F[(n - 1) + 1;t]/r((n - 1)!)) * b - t^n - 1 dt))
9. F : ℕn + 2 ⟶ I ⟶ℝ
10. ∀k:ℕn + 2. ∀x,y:{a:ℝ| a ∈ I} .  ((x = y) 
⇒ (F[k;x] = F[k;y]))
11. finite-deriv-seq(I;n + 1;i,x.F[i;x])
12. λt.((F[n + 1;t]/r((n)!)) * b - t^n) ∈ {f:[rmin(a;b), rmax(a;b)] ⟶ℝ| ifun(f;[rmin(a;b), rmax(a;b)])} 
⊢ Taylor-remainder(I;n;b;a;k,x.F[k;x]) = a_∫-b (F[n + 1;t]/r((n)!)) * b - t^n dt
Latex:
Latex:
1.  I  :  Interval
2.  iproper(I)
3.  a  :  \{a:\mBbbR{}|  a  \mmember{}  I\} 
4.  b  :  \{a:\mBbbR{}|  a  \mmember{}  I\} 
5.  [rmin(a;b),  rmax(a;b)]  \msubseteq{}  I 
6.  n  :  \mBbbZ{}
7.  0  <  n
8.  \mforall{}F:\mBbbN{}(n  -  1)  +  2  {}\mrightarrow{}  I  {}\mrightarrow{}\mBbbR{}
          ((\mforall{}k:\mBbbN{}(n  -  1)  +  2.  \mforall{}x,y:\{a:\mBbbR{}|  a  \mmember{}  I\}  .    ((x  =  y)  {}\mRightarrow{}  (F[k;x]  =  F[k;y])))
          {}\mRightarrow{}  finite-deriv-seq(I;(n  -  1)  +  1;i,x.F[i;x])
          {}\mRightarrow{}  (Taylor-remainder(I;n  -  1;b;a;k,x.F[k;x])
                =  a\_\mint{}\msupminus{}b  (F[(n  -  1)  +  1;t]/r((n  -  1)!))  *  b  -  t\^{}n  -  1  dt))
9.  F  :  \mBbbN{}n  +  2  {}\mrightarrow{}  I  {}\mrightarrow{}\mBbbR{}
10.  \mforall{}k:\mBbbN{}n  +  2.  \mforall{}x,y:\{a:\mBbbR{}|  a  \mmember{}  I\}  .    ((x  =  y)  {}\mRightarrow{}  (F[k;x]  =  F[k;y]))
11.  finite-deriv-seq(I;n  +  1;i,x.F[i;x])
\mvdash{}  Taylor-remainder(I;n;b;a;k,x.F[k;x])  =  a\_\mint{}\msupminus{}b  (F[n  +  1;t]/r((n)!))  *  b  -  t\^{}n  dt
By
Latex:
Assert  \mkleeneopen{}\mlambda{}t.((F[n  +  1;t]/r((n)!))  *  b  -  t\^{}n)  \mmember{}  \{f:[rmin(a;b),  rmax(a;b)]  {}\mrightarrow{}\mBbbR{}| 
                                                                                              ifun(f;[rmin(a;b),  rmax(a;b)])\}  \mkleeneclose{}\mcdot{}
Home
Index